Advanced analysis to supplement HAZOP/LOPA for effective process design. Issue 2 (28th September 2016) - Banick, William R.; Wei, Cindy
Abstract : The HAZOP and LOPA methods are commonly used for qualitative hazard identification and semi‐quantitative assessment of risk in the process industries. Integration of HAZOP and LOPA techniques into a single study has provided the practical advantage of utilizing the same team of subject matter experts to complete evaluation of hazard scenarios, identify needs for further risk reduction, recommend specific safeguards required and confirm resulting residual risk is acceptable. While practical and efficient, the one‐step comprehensive integrated HAZOP/LOPA method can have pitfalls. In particular, use of LOPA alone to confirm risk acceptability can lead to complex solutions to meet order‐of‐magnitude threshold requirements for risk reduction and restrictive requirements for independent protection layers (IPLs). Quantitative methods are sometimes required beyond HAZOP/LOPA to obtain a more precise evaluation of identified hazards and benefits of the associated safeguards. This article presents a risk assessment approach incorporating advanced analysis, including human factors task, fault tree and cost‐benefit analysis, following HAZOP/LOPA analysis. To illustrate this approach, an example is shown on the selection of appropriate engineering design options for cyclic regeneration of dense phase ethylene treaters, which have unique safety concerns. Using advanced analysis, a cost effective design solution is developed and is shown to reduce risk to as low as reasonably practicable (ALARP). © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 192–201, 2017